Plasma fibrinogen levels towards cancer incidence: a systematic review and meta-analysis of epidemiological studies - Yuexin Luo; Furong Lu; Lihua Luo; Yuting Li (Discover Oncology)
Abstract Importance Understanding the association between fibrinogen levels and cancer incidence is crucial for elucidating potential diagnostic and therapeutic implications in oncology. Objective This meta-analysis aimed to comprehensively evaluate the relationship between circulating fibrinogen levels and various tumour types. Registration This systematic review had been registered in PROSPERO (ID: CRD42024616015). Data sources A systematic review search was performed on PUBMED, EMBASE and Cochrane databases until June 3, 2023. Study selection Studies that fulfilled our pre-established inclusion criteria were incorporated into our analysis. These criteria encompassed prospective cohort, case–control, and nested case–control designs, all featuring histopathologically confirmed primary cancers. Furthermore, we included studies that had reported odds ratios (ORs), relative ratios (RRs) or hazard ratios (HRs) along with their corresponding 95% confidence intervals (95% CIs), ensuring the reliability and comparability of the data across studies. Data extraction and synthesis Two independent authors meticulously extracted data from eligible studies, ensuring rigour and accuracy. Subsequently, we performed statistical analyses using the robust STATA version 12.0 software, guaranteeing the reliability of our findings. Moreover, we carried out in-depth subgroup analyses, categorizing studies based on tumour type, to meticulously explore and quantify the variations in the correlation between fibrinogen levels and tumour incidence. Through this approach, we have gained a nuanced understanding of the potential heterogeneity of this relationship across different cancer types. Main outcomes and measures The major outcome of this study centred on elucidating the relationship between fibrinogen levels and cancer incidence, with subsequent subgroup analyses conducted to delve deeper into this relationship within specific tumour types. This approach aimed to provide a comprehensive understanding of how fibrinogen levels may varying influence different cancer types, thereby offering potential insights into the identification of novel risk factors or biomarkers for further clinical investigation. Results Twelve studies were meticulously incorporated into the meta-analysis. Notably, significant heterogeneity was observed across these studies, necessitating careful interpretation of the results. The meta-analysis demonstrated a compelling connection between elevated fibrinogen levels and an increased risk of cancer incidence, with an hazard ratio (HR) of 1.33 (95% CI: 1.16, 1.51; p = 0.000), demonstrating a statistically significant finding. Further subgroup analyses delved into specific cancer types and identified significant associations with smoking-related cancer (HR = 1.79; 95% CI: 1.54, 2.09; p = 0.000), lung cancer (HR = 1.98; 95% CI: 1.62, 2.43; p = 0.000) and colorectal cancer (HR = 1.27; 95% CI: 1.00, 1.62; p = 0.048). These findings underline the potential significance of fibrinogen levels as a potential biomarker or risk factor for these particular cancer types. Conclusions and relevance Elevated plasma fibrinogen levels have been significantly associated with an increased incidence of cancer, particularly in the cases of lung and colorectal cancers. These compelling findings underscore the potential value of fibrinogen levels as a diagnostic or prognostic biomarker in cancer management. Accordingly, further studies and clinical validation are urgently needed to fully explore the role of fibrinogen in cancer and its potential application in clinical practice.